PGC-1α promotes the survival of newborn neurons within AD hippocampus through activation of the FNDC5/BDNF/TrkB signaling pathway - Wang, Yi-Jie; Wang, Yu-Xin; Zou, Cheng-Zhi; Zhang, Wei-Jun; Pan, Wen; Wang, Jia-Qing; Wang, Hua; Qian, Xin; Han, Guo-Jia-Hao; Liu, Feng-Guo; Wang, Jia (Frontiers in Molecular Neuroscience, 2025)
BackgroundThe learning and memory impairments observed in Alzheimer’s disease (AD) are strongly associated with impaired neurogenesis in the hippocampal region. Our previous research has highlighted the potential of peroxisome proliferator-activated receptor gamma coactivator-1 alpha (PGC-1α) in ameliorating AD-related pathological changes. As a key metabolic regulator, PGC-1α is highly expressed in energy-demanding tissues such as the hippocampus. However, its specific roles and underlying mechanisms in AD-associated neurogenesis remains largely unclear.ObjectiveThis study aimed to elucidate the precise role and molecular mechanisms by which PGC-1α regulates the survival of newly generated neurons during neurogenesis in the AD-affected hippocampus.MethodsUsing combined models of PGC-1α overexpression in the hippocampal dentate gyrus (DG) of AD-model mice and PGC-1α knockout mice, we investigated the effects of gain- and loss-of-function of PGC-1α on the regulation of the FNDC5/BDNF/TrkB signaling pathway, as well as on the survival of newborn neurons in the AD-affected hippocampus.ResultsOur findings demonstrate that PGC-1α enhances the survival of newly generated neurons in the AD-affected hippocampus. Furthermore, PGC-1α functions acts as an upstream regulator of the FNDC5/BDNF/TrkB signaling pathway, and its knockdown suppresses neuronal survival by inhibiting this pathway.ConclusionThese results indicate that PGC-1α serves as a critical mediator in the FNDC5/BDNF/TrkB signaling pathway within newborn neurons. Enhancing PGC-1α expression, either pharmacologically or through alternative approaches, may therefore represent a promising therapeutic strategy for Alzheimer’s disease.